Clear Aligners in the Growing Patient: A Systematic Review - Alessio Danilo Inchingolo; Gianna Dipalma; Irene Ferrara; Fabio Viapiano; Anna Netti; Anna Maria Ciocia; Antonio Mancini; Giuseppina Malcangi; Andrea Palermo; Angelo Michele Inchingolo; Francesco Inchingolo (MDPI AG, 2024)
Mixed dentition represents a critical phase in the oral development of pediatric patients, characterized by the simultaneous presence of primary and permanent teeth. This article proposes a comprehensive systematic review of the application of aligners as an innovative methodology in managing mixed dentition. The primary objective is to explore the efficacy, safety, and acceptability of this emerging orthodontic technology in the evolving age group. This systematic review focuses on randomized controlled trials, cohorts, and observational studies investigating the use of aligners in patients with mixed dentition. Clinical, radiographic, and psychosocial parameters will be considered to assess the overall impact of aligner therapy in this critical phase of dental development. An in-depth analysis of such data aims to provide a comprehensive overview of the potential of this technology in pediatric orthodontics. Expected outcomes may contribute to outlining practical guidelines and targeted therapeutic strategies for orthodontists involved in managing mixed dentition. Furthermore, this article aims to identify gaps in the current research and suggest future directions for studies exploring the use of transparent aligners in patients with mixed dentition, thereby contributing to the ongoing evolution of evidence-based orthodontic practices.